Assessment of Pharmacists’ Knowledge and Competence Regarding Anti-Tobacco Counseling - Justyna Dymek; Agnieszka Skowron (Pharmacy, 2013)
The aim of the study was to assess Polish community pharmacists’ knowledge about the health consequences of smoking and the abilities they need in professional advice-giving during the smoking cessation process. Therefore, we use a self-answered questionnaire to assess pharmacists’ knowledge about the health consequences of smoking and his/her abilities in NRT advice-giving. In total, the pharmacists could earn 20 points, 14 in the knowledge section and 6 in the abilities section. One hundred and nine pharmacists from community pharmacies were included, 87 of whom were women (79%). The average age of respondents was 38 years (24–72). The mean knowledge rating of pharmacists regarding the health risk factors connected with smoking was 7.7 points (SD = 2.2), the maximum was 14. None of the respondents obtained the maximum possible score in the test. Only 2.7% of pharmacists correctly identified all four factors important in selecting the form of NRT. Analysis showed that pharmacists’ knowledge about tobacco dependence and tobacco-related diseases is insufficient for an effective tobacco control interventions. It seems necessary to undertake systematic training to improve their knowledge about nicotine addiction and abilities in NRT and smoking cessation advice-giving.